EFFECTS OF VIBRATION TRAINING IN DEGENERATIVE CEREBRAL MICROANGIOPATHY ON MOTOR PERFORMANCE. Issue 10 (10th June 2013) - Nitzsche, Nico; Reinhardt, Fritjof
Abstract : Background: The degenerative cerebral microangiopathy (CMA) is a disease penetrating brain arteries with the result of single or multiple acute small subcortical infarcts with or without associated leukoencephalopathy. The consequences are focal neurological deficits, gait and balance disorders, and vascular dementia (de Laat. 2010 & 2012). Previously, stimulus set showed in neurological degenerative diseases due to the high density stimulus positive effects on motor activity (del Pozo Cruz et al 2012; Claerbout et al 2012). The prevalence in people over 60 years is at 20–30%. The pilot study was to examine the goal of a multi-week vibration training on motor performance of patients. Methods: Thirty-two patients (72.7±8.5 years, BMI 28.9±4.3 kg/m 2 ) with mild to moderate CMA were studied before and after training on postural control (C1=Condition 1 & C2=Condition 2), isometric trunk strength, hand strength response and quality of life (SF 36). The measurements of postural control were in the upright position on an unstable platform and have a quiet place with disturbance (Haider Posturomed®). The oscillation travel (s) and oscillation velocity (v) (Noraxon® 6g) of the stood plate were observed. The strength of the hull (anterior/posterior) and the hand (Vernier®) were measured isometrically (Dr. Wolf® Back Check). The assessment of gait (30m) was performed using an inertial sensor (Lokometrix®). A thirty meters distance has been covered. Step frequency, stride length, walking speed and symmetry were measured. Training was performed 3 times weekly for 10 weeks on a vibration plate (Galileo®) with sinusoidal oscillations. Static and dynamic exercises were used while standing. Results: There were completed 23±3.2 training sessions (16.7±4 minutes. 20.5±4.6 Hz. A=4mm). Postural control (C1: sprä=0.66±0.9 m vs. spost=0.33±0.3 m; vprä=4.4±5.6 m/s vs. vpost=2.5±3.9 m/s. C2: speed: vprä=9.1±6.2 m/s; vpost=6.2±3.2 m/s; sprä: 1.0±0.8 m; spost 0.5±0.2 m) improved in both conditions significantly (p<0.01). There were significant increases in isometric trunk strength (ventral: 2.8±1.3 to 3.3±1.4 N/kg; dorsal: 3.4±1.8 to 3.9±2.1 N/kg; p<0.01) and improvements in five of eight items in quality of life (physical function, role function of physical body, general health, social functioning, emotional role; p<0.01). Changes in gait and hand strength were not available (p>0.05). Discussion: Initial findings by vibration training on motor performance could be gained. Several weeks of vibration training could become a key therapeutic approach for Training CMA present affecting the motor skills disorders positively. Postural control and quality of life appear as signficantly improved values. Often these are important requirements for activation of bodys. The next step should be followed by a randomized trial.